Physiological and cultivation requirements of Trametes versicolor, a medicinal mushroom to diversify Indian mushroom industry - Veena, S S; Pandey, Meena (The Indian Journal of Agricultural Sciences, 2012)
Tramete versicolor (known as “turkey tail”) is one of the most potent, and the best studied, of all medicinal mushrooms. This mushroom is known to possess anti cancer, anti viral properties and stimulates the immune system. It is native to tropical, subtropical and temperate zones and is highly adaptive. No attempt had been made in India to cultivate this precious mushroom. T. versicolor was collected from Sampaje forest area of Coorg, Karnataka (Western ghats), India. It occurred as a classic bracket fungus with multicolored, closely concentric zonations with slightly hairy surface, the stem was central and short. Pure culture was made on MEA and the cultural requirements were studied. The ambient temperature and pH for the mycelial growth was 25 °C and 4.5 to 6.0 respectively. The maximum mycelial growth was observed on MEA (14.93 mm/day), mycelium was pure white in color and moderately fluffy. The spawn was made on sorghum grain and the fructification was attempted on sawdust 90% + rice bran 10% substrate formulation. Spawn run was completed within 18–20 days at 25± 2 °C. Fructification was observed at 25 ± 2 °C and 80-85% R H. This is the first report of successful cultivation of T. versicolor from India. Successful cultivation of this mushroom will play a key role in the diversification of mushroom industry in India.